Connection to nature for sustainable development at universities—What should be done? - Kleespies, Matthias Winfried; Dierkes, Paul Wilhelm (Frontiers in Sustainability, 2023)
Universities and institutions of higher education play an important role in today's society. They educate the next generation of decision-makers and therefore have a great influence on the decisions made in society. In today's world, where many people's livelihoods are threatened by environmental issues, it is not only necessary for universities to operate sustainably, but also to motivate students to adopt more sustainable behaviors. We believe that promoting a connection to nature is an important starting point for this, as it is a key influencing factor for sustainable behavior. Due to decreasing contact with nature and increasing urbanization worldwide, connection to nature is currently in decline.In this perspectiveBased on the current literature, we propose six starting points that can help increase the connection to nature of university students: (1) Bringing students to nature, (2) bringing nature to students, (3) environmental education, (4) virtual nature contact, (5) incorporating other human-nature relationships and concepts (6) combining 1-5. For each point, we explain possible recommendations for university decision-makers.